2011
DOI: 10.1186/1471-2148-11-255
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of Adh and LEAFY and the phylogenetic utility of their introns in Pyrus (Rosaceae)

Abstract: BackgroundThe genus Pyrus belongs to the tribe Pyreae (the former subfamily Maloideae) of the family Rosaceae, and includes one of the most important commercial fruit crops, pear. The phylogeny of Pyrus has not been definitively reconstructed. In our previous efforts, the internal transcribed spacer region (ITS) revealed a poorly resolved phylogeny due to non-concerted evolution of nrDNA arrays. Therefore, introns of low copy nuclear genes (LCNG) are explored here for improved resolution. However, paralogs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 84 publications
5
21
0
Order By: Relevance
“…In addition, the Oriental pear cluster contained two subgroups: A1, consisting of three P. betulifolia accessions, and A2, which clustered the other cultivars and species together. The position of P. betulifolia at the first independent branch in the Oriental pears might be related to its older origin (Zheng et al, 2011), which was confirmed by recent phylogenetic research from our research group (unpublished data). The species and cultivars in A2 displayed a complex relationship with a lower confidence coefficient, probably due to wide hybridization within Pyrus (Aldasoro et al, 1996).…”
Section: Assessment Of the Genetic Relationship Among 28 Pyrus Accesssupporting
confidence: 84%
See 3 more Smart Citations
“…In addition, the Oriental pear cluster contained two subgroups: A1, consisting of three P. betulifolia accessions, and A2, which clustered the other cultivars and species together. The position of P. betulifolia at the first independent branch in the Oriental pears might be related to its older origin (Zheng et al, 2011), which was confirmed by recent phylogenetic research from our research group (unpublished data). The species and cultivars in A2 displayed a complex relationship with a lower confidence coefficient, probably due to wide hybridization within Pyrus (Aldasoro et al, 1996).…”
Section: Assessment Of the Genetic Relationship Among 28 Pyrus Accesssupporting
confidence: 84%
“…In addition, P. ussuriensis and 'Yali' formed a branch in agreement with Yao (2010). 'Cili', another cultivar from the P. pyrifolia white pear group, clustered with P. pyrifolia from Japan, which supports the viewpoint that Chinese white pears are a variety or ecotype of P. pyrifolia (P. pyrifolia white pear group) (Teng and Tanabe, 2004;Bao et al, 2007;Zheng et al, 2011).…”
Section: Assessment Of the Genetic Relationship Among 28 Pyrus Accesssupporting
confidence: 57%
See 2 more Smart Citations
“…genus is variously said to consist of from 20 to over 70 wild or domesticated species [22][23][24][25]. It is relatively difficult to give an accurate number of pear species, because they easily cross-pollinate and the obtained crosses have ambiguous taxonomic status.…”
Section: Introductionmentioning
confidence: 99%